2016
DOI: 10.1080/10799893.2016.1247861
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and pharmacological effects of a novel GPR142 antagonist

Abstract: GPR142 is a G-protein-coupled receptor (GPCR), whose most potent and efficacious ligand has been reported as being the natural amino acid l-tryptophan. GPR142 is highly expressed in pancreatic β-cells and immune cells, suggesting the receptor may play a role in the pathogenesis and development of diabetes or inflammatory diseases. In a previous report, we developed GPR142 agonists as insulin secretagogues. In this report, we show the discovery of a selective, potent small-molecule GPR142 antagonist, CLP-3094, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…However, recent data suggest that serum tryptophan levels are increased in T2DM patients with a higher degree of insulin resistance (Chen et al, 2016), suggesting that inhibition of the receptor could prove beneficial. Furthermore, Gpr142 2/2 mice display reduced levels of sensitivity to a collagen antibody-induced arthritis model of inflammation (Murakoshi et al, 2016). A similar effect was observed with a GPR142 antagonist (CLP-3094) (Murakoshi et al, 2016).…”
Section: J Gpr142mentioning
confidence: 67%
See 1 more Smart Citation
“…However, recent data suggest that serum tryptophan levels are increased in T2DM patients with a higher degree of insulin resistance (Chen et al, 2016), suggesting that inhibition of the receptor could prove beneficial. Furthermore, Gpr142 2/2 mice display reduced levels of sensitivity to a collagen antibody-induced arthritis model of inflammation (Murakoshi et al, 2016). A similar effect was observed with a GPR142 antagonist (CLP-3094) (Murakoshi et al, 2016).…”
Section: J Gpr142mentioning
confidence: 67%
“…Furthermore, Gpr142 2/2 mice display reduced levels of sensitivity to a collagen antibody-induced arthritis model of inflammation (Murakoshi et al, 2016). A similar effect was observed with a GPR142 antagonist (CLP-3094) (Murakoshi et al, 2016). Identification of better tool compounds will enable greater target validation and clarification of the pathophysiological processes controlled by GPR142.…”
Section: J Gpr142mentioning
confidence: 81%
“…200 Cxcr2 knockout mice had attenuated autoantibody-mediated arthritis caused by a function of Cxcr2 neutrophil recruitment, 201 while Gpr142 knockout mice showed reduced arthritis scores and disease incidence in an anti-type II collagen antibody-induced arthritis model alongside decreased inflammatory cytokine production. 202 Mader et al found that while Ccr2 −/− mice had larger and stronger bones than wild-type mice, they reported that Ccr2 loss did not significantly protect against bone loss due to disuse or estrogen loss. 203 Ccr5 deletion was linked to reduced cartilage degeneration postsurgery without significant changes in the degree of synovitis and bone metabolic parameters 204 and promoted osteoclast function in orthodontic tooth movement.…”
Section: Diseases or Dysfunction Caused By Gpcr Mutation Or Deletion mentioning
confidence: 99%
“…The human receptor orthologs of MIP receptors are GPR139 and GPR142, two orphan GPCRs for which neither the endogenous ligand nor the function has been elucidated. GPR139 is predominantly expressed in specific areas of the human and mouse CNS, including the amygdala and hippocampus, whereas GPR142 displays a more ubiquitous expression both in the CNS and in various peripheral glands and organs [31,58,59]. Interestingly, it has been shown, for example, that avoidance learning in humans correlates with activation of amygdala [31,58,59]…”
Section: Discussionmentioning
confidence: 99%